2008
DOI: 10.1063/1.2943147
|View full text |Cite
|
Sign up to set email alerts
|

Optical excitations of defects in realistic nanoscale silica clusters: Comparing the performance of density functional theory using hybrid functionals with correlated wavefunction methods

Abstract: Optical excitations of low energy silica (SiO(2))(4) clusters obtained by global optimization, as opposed to constructed by hand, are studied using a range of theoretical methods. By focusing on the lowest energy silica clusters we hope to capture at least some of the characteristic ways by which the dry surfaces of silica nanosystems preferentially terminate. Employing the six lowest energy (SiO(2))(4) cluster isomers, we show that they exhibit a surprisingly wide range of geometries, defects, and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…There exists a significant number of works comparing TD‐DFT and wavefunction transition energies, the latter being often obtained with the CC2 or CCSD methods. Most of these investigations are focused on a rather small panel of compounds and we briefly summarize selected examples in this Section.…”
Section: Comparisons With Theoretical Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…There exists a significant number of works comparing TD‐DFT and wavefunction transition energies, the latter being often obtained with the CC2 or CCSD methods. Most of these investigations are focused on a rather small panel of compounds and we briefly summarize selected examples in this Section.…”
Section: Comparisons With Theoretical Valuesmentioning
confidence: 99%
“…These errors were found to decrease when corrections for the asymptotic behavior of the XCF were included . Zwijnenburg et al compared CAS‐PT2, B3LYP, and BB1K descriptions of the ES of (SiO 2 ) 4 clusters and found that the latter functional better reproduced CAS‐PT2 values . For DNA bases and base pairs, Shukla and Leszczynski, compared CC2/def2‐TZVP excitation energies to TD‐DFT values in both gas and solvent phases .…”
Section: Comparisons With Theoretical Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2g shows the typical HRTEM image of one nanowire without any crystalline domains, indicating that the nanowire is amorphous, which is confirmed by the selected area electron diffraction (SAED) pattern with only diffusive rings instead of diffraction spots, shown as an inset in Figure 2g. Optical devices will have more functions on each chip if silica nanostructures with different morphologies originating from silica nanowires that are integrated [11,13,14]. …”
Section: Resultsmentioning
confidence: 99%
“…Rope-like silica nanowire assemblies showing reversible blue light emission behavior in photoluminescence and infrared analysis could be used to fabricate effective optoelectronic devices and optical signal humid sensors [12]. Theoretical calculations have also been conducted to explore some interesting optical properties of silica nanoclusters [13,14]. Up to the present, many approaches have been introduced to synthesize silica nanostructures [15-19], and various morphologies were reported, such as nanowire assemblies [17,20], nanoflowers [21], nanotubes [22], and nanosprings, [23] etc.…”
Section: Introductionmentioning
confidence: 99%